2018
DOI: 10.1101/370544
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PIP4Ks Suppress Insulin Signaling Through a Catalytic-Independent Mechanism

Abstract: Insulin stimulates conversion of phosphatidylinositol-4,5-bisphosphate (PI(4,5)P2) to 4,4,5)P3), which mediates downstream cellular responses. PI(4,5)P2 is produced by phosphatidylinositol-4-phosphate 5kinases (PIP5Ks) and byphosphatidylinositol-5-phosphate 4-kinases (PIP4Ks). Here we show that deletion of the three genes that encode PIP4Ks (PIP4K2A, PIP4K2B and PIP4K2C) in vitro results in a paradoxical increase in PI(4,5)P2 and a subsequent increase in insulin-stimulated production of PI(3,4,5)P3. Surprising… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…However, a link between the levels of the two lipids cannot be ruled out completely. Interestingly, a recent study has reported that cells depleted of PIP4K show elevated levels of PIP2 and PIP3; evidence is presented that the interaction of PIP5K, the enzyme that synthesizes the majority of PIP2 cells, is inhibited by its interaction with PIP4K (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, a link between the levels of the two lipids cannot be ruled out completely. Interestingly, a recent study has reported that cells depleted of PIP4K show elevated levels of PIP2 and PIP3; evidence is presented that the interaction of PIP5K, the enzyme that synthesizes the majority of PIP2 cells, is inhibited by its interaction with PIP4K (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, while interactions between the type I PIP5K and type II PIP4K isoforms have been documented previously, more recent studies now define an important kinase‐independent role for PIP4Ks in the indirect regulation of PtdIns(4,5)P 2 levels within the PM . This unique mechanism involves the allosteric inhibition of PIP5Ks through a conserved N‐terminal motif . These studies stress the continued importance of exploring the non‐catalytic functions of PPIn‐modifying enzymes as well as the potential impact of targeting these types of allosteric interactions in drug discovery efforts.…”
Section: Production Of Polyphosphoinositide Species Within the Pmmentioning
confidence: 84%
“…It has also been postulated that the true function of the PIP4Ks might actually be related to the maintenance of PtdIns5P levels, rather than for contributing to local PtdIns(4,5)P 2 production . However, while interactions between the type I PIP5K and type II PIP4K isoforms have been documented previously, more recent studies now define an important kinase‐independent role for PIP4Ks in the indirect regulation of PtdIns(4,5)P 2 levels within the PM . This unique mechanism involves the allosteric inhibition of PIP5Ks through a conserved N‐terminal motif .…”
Section: Production Of Polyphosphoinositide Species Within the Pmmentioning
confidence: 99%
“…The type 2 phosphatidylinositol-5-phosphate 4-kinases (PI5P4Ks), composed of a family of 3 isoforms (α, β and γ), catalyze the formation of phosphatidylinositol 4,5-bisphosphate (PI-4,5-P 2 ) by phosphorylating phosphatidylinositol 5-phosphate (PI-5-P) at the 4 position of the inositol ring. These kinases play a role in a variety of disease states, including cancer, insulin signaling, and oxidative stress (Carricaburu et al, 2003;Emerling et al, 2013;Jones et al, 2006;Jones, Foulger, Keune, Bultsma, & Divecha, 2013;Jude et al, 2015;Keune et al, 2012;Sharma, Mathre, Ramya, Shinde, & Raghu, 2019;Wang et al, 2019).…”
mentioning
confidence: 99%
“…Furthermore, they regulate early endosomal homeostasis during clathrin-mediated endocytosis, a key step in synaptic vesicle trafficking (Kamalesh et al, 2017). Of particular interest, these enzymes also play a major role in suppressing the activity of the type 1 phosphatidylinositol-4-phosphate 5-kinases through direct binding to these enzymes (Wang et al, 2019). Although the expression and function of these kinases have been explored in oncogenic signaling pathways and in settings of nutrient stress, few studies have examined their role in the brain.…”
mentioning
confidence: 99%